The Principal as a Catalyst for Change: Innovative Strategies to Improve the Quality of Senior High School Education: The Principal as a Catalyst for Change: Innovative Strategies to Improve the Quality of Senior High School Education - Ahmad Walid; Ja'far Shodiq; Mutmainnah Mutmainnah (Innovative Pedagogy and Education Studies, 2024)
The principal plays a crucial role as a key agent of change in improving the quality of senior high school education. This study aims to examine the innovative strategies implemented by school principals in enhancing educational quality, particularly in the areas of instructional leadership, school management, teacher professional development, and the creation of a positive school culture. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis involving principals, teachers, and school staff. The findings reveal that effective principals demonstrate visionary leadership, encourage collaborative practices, integrate technology in school management and learning processes, and continuously support teachers’ professional growth. These strategies contribute significantly to improving teaching effectiveness, student achievement, and overall school performance. The study concludes that principals who act as catalysts for change are able to transform schools into adaptive, innovative, and high-quality educational institutions. The results of this research are expected to provide insights for school leaders, policymakers, and educational stakeholders in developing effective leadership practices in senior high schools.